Estudo da estrutura populacional, caracterização molecular de Aniba rosaeodora (Ducke) pau-rosa em áreas de distribuição potencial do distrito de Masisea, Ucayali, Peru. - Revilla, Jorge Chávez [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Aniba rosaeodora Ducke, known as "rosewood", is one of the most valuable tree species in the Amazon, famous for its linalool-rich essential oil, used in the cosmetics industry. However, their overexploitation has led to the decrease of their natural populations, affecting their production and genetic diversity, putting the species at risk of extinction. The species is found mainly in forests in Brazil, Colombia, Ecuador, Peru and other countries in the Amazon region, growing in habitats of plateaus and streams, and can reach up to 30 m in height. Seed dispersal depends on animals such as parrots and toucans, but their natural regeneration is threatened by predation and other factors. This study seeks to better understand the patterns of dispersion, density and population dynamics of A. rosaeodora in the Peruvian Amazon, in order to propose strategies for its conservation and forest management. Population dynamics play a key role in the conservation and domestication of species. From genetic assays of forest species in the Peruvian Amazon, methodologies were developed to evaluate the phenotypic variation of their traits of commercial interest. These methodologies were applied in conservation and domestication studies, through stability, adaptability and productivity tests of progenies of Guazuma crinita Mart, in addition to the qualitative and quantitative control of phenotypes of Calycophyllum spruceanum Benth. These studies, carried out in the Aguaytía river basin in the Peruvian Amazon, can be adapted for methodological application in Aniba rosaeodora Ducke in the region, with the aim of promoting its conservation and sustainable management.

Aniba rosaeodora Ducke, conhecido como "pau-rosa", é uma das espécies arbóreas mais valiosas da Amazônia, famosa pelo seu óleo essencial rico em linalol, utilizado na indústria cosmética. No entanto, sua sobre-exploração tem levado à diminuição de suas populações naturais, afetando sua produção e diversidade genética, colocando a espécie em risco de extinção. A espécie é encontrada principalmente em florestas do Brasil, Colômbia, Equador, Peru e outros países da região amazônica, crescendo em habitats de platôs e riachos, podendo atingir até 30 m de altura. A dispersão das sementes depende de animais como papagaios e tucanos, mas sua regeneração natural está ameaçada pela predação e outros fatores. Este estudo busca entender melhor os padrões de dispersão, densidade e dinâmica da população de A. rosaeodora na Amazônia peruana, a fim de propor estratégias para sua conservação e manejo florestal. A dinâmica populacional desempenha um papel fundamental na conservação e domesticação das espécies. A partir de ensaios genéticos de espécies florestais na Amazônia peruana, foram desenvolvidas metodologias para avaliar a variação fenotípica de seus caracteres de interesse comercial. Essas metodologias foram aplicadas em estudos de conservação e domesticação, por meio de testes de estabilidade, adaptabilidade e produtividade de progênies de Guazuma crinita Mart, além do controle qualitativo e quantitativo de fenótipos de Calycophyllum spruceanum Benth. Esses estudos, realizados na bacia do rio Aguaytía, na Amazônia peruana, podem ser adaptados para aplicação metodológica em Aniba rosaeodora Ducke na região, com o objetivo de promover sua conservação e manejo sustentável.
Study of population structure, molecular characterization of Aniba rosaeodora (Ducke) rosewood in areas of potential distribution of Masisea district, Ucayali, Peru.
Keywords: Amazon forest; Rosewood; Population density; Population structure; Seedling dispersal; Biomass; Allometric model; Progeny test; White bolaina; GxE interaction; Capirona